THE CONCEPT “MOTHER/AHA” IN PROVERBS OF THE KARAKALPAK LANGUAGE - Usenova, G.; Seytjanova, L.T. (SCIENCE and SOCIETY, 2016)
The given article deals with the definitional and componential analysis of the concept ―mother/ ана‖ in proverbs of the Karakalpak language. The aim of the article is the analysis and description of proverbs containing the concept ―Mother/Ана‖ in the Karakalpak language. In the article the following methods are used: definitional, componential and descriptive analysis. The present concept is universal, it has the meanings, including customs, traditions and beliefs, characterized for Karakalpak culture.
Keywords: concept; paremii; national linguoculture; cognitive linguistics